Peace and security : implications for women - Porter, Elisabeth, 1955-; Mundkur, Anuradha (New approaches to peace and conflict., 2012)
Offering a broad overview of what is being done in conflict-affected countries to advance women's participation in peace processes, peace building, and decision making, this record examines the implementation of UN Security Council Resolution 1325 on Women, Peace, and Security and presents evidence-based case studies from East Timor, Fiji, and Sri Lanka. As it explores ways to protect women and girls from violence, it suggests key actions that should be taken by development agencies, women's nongovernmental organizations, and policymakers. The book focuses on the following fundamental aspects: a specifically feminist methodology, a priority on gender equality and women's empowerment, and the broad notions of human security and peace building.